Youth Moral Construction Strategy in the Development of Islamic Dakwah Through Religious Activities - Burhanuddin, Burhanuddin; Sabri, Yuli; Amrt, Endyn; Ferc, Elexf (Journal International Dakwah and Communication, 2022)
Today, various problems are being faced by the younger generation of Indonesia. The increasingly advanced and modern times have triggered a crisis of Noble Characters. One of the causes of the current Noble Characters crisis is that humans have paid less attention to religious teachings, especially among young people who are synonymous with promiscuity. The currents of globalization have given birth to new patterns of association that tend to undermine the morals of the younger generation. This is marked by the proliferation of western life patterns in Indonesia. As well as triggering selfishness, selfishness, and the fading of the value of manners in humans, and youth, in particular, Da'wah is a forum as well as the most important sector in the formation of Islamic youth as agents of the change in the spread of Islam. In proselytizing, there is a process of organizing activities or efforts that are carried out consciously and deliberately in an effort to improve the standard and value system of human life based on the provisions of Allah and Rasulullah 'Sallallahu 'Alaihi Wasallam. In other words, Islamic proselytizing aims to invite the human ummah with wisdom (wisdom) to follow the instructions of Allah and Rasulullah. This effort can be made by the coach either directly or indirectly directly if the coaching efforts are carried out by the coach to the party fostered in the activity indirectly if the problem-solving efforts are carried out by the coach through other parties.